Exploration of Teachers' Understanding of the Independent Curriculum and Its Impact on the Quality of Teaching in Elementary Schools: Eksplorasi Pemahaman Guru Tentang Kurikulum Merdeka dan Dampaknya Terhadap Kualitas Pengajaran di Sekolah Dasar - Nur Aisah; Ahmad Hariandi; Andi Gusmaulia Eka Putri (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2025)
This research aims to describe how teachers understand the Merdeka curriculum and its impact on the quality of teaching in elementary schools. This research uses a qualitative approach with a case study type of research. This research was carried out at SDN 198/1 Pasar Baru in the even semester 2024/2025. The research subject is Mrs. K as the homeroom teacher. This research data was obtained through observation, interviews and document study. Data validation test using triangulation. The results of this research indicate that class I teachers understand the Independent Curriculum well. However, there are still obstacles such as difficulties in adapting learning technology, lack of time to attend training, and lack of confidence in changing traditional teaching methods. These obstacles affect the effectiveness of teaching, good thinking about the curriculum can still improve the quality of learning in the classroom. A guide for use in teaching that directs teachers through important steps such as planning, implementation, management, as well as assessing and reporting results. Teachers have flexibility depending on the design of learning steps, so that this success is reflected in student learning outcomes reports which reflect the extent to which students follow the learning.